Multivariate Insight into Seasonal Hydrogeochemical Dynamics of the Thrissur–Ponnani Kole Wetlands, Central Kerala - Mohammed, Samreena; K. S, Arun kumar; V, Santhosh (Journal of Neonatal Surgery, 2025)
Groundwater in Kerala’s Thrissur–Ponnani Kole wetlands is increasingly threatened by seawater intrusion, agrochemical loading, and untreated effluents. To diagnose these pressures, we sampled 70 shallow wells during pre-monsoon, monsoon, and post-monsoon seasons (2022–2023) and measured 13 physico-chemical parameters. Multivariate analyses—Pearson correlation, hierarchical clustering, factor analysis, and principal component analysis—were applied to 2,730 observations. Electrical conductivity, salinity, and total dissolved solids exhibited a strong inter-correlation (r > 0.90), signalling chronic marine ingress. Six principal components accounted for 91.9 % of total variance: PC1 captured saline and domestic inputs, PC2 reflected carbonate weathering, and PC3 highlighted fertiliser-derived nutrients. Seasonal clustering revealed evaporative concentration and nutrient enrichment pre-monsoon, rainfall-driven dilution during monsoon, and partial salinity rebound post-monsoon. Seawater intrusion and agricultural leachate thus emerge as the dominant, seasonally modulated threats to the aquifer. We recommend a tiered monitoring framework—combining seasonal pumping controls with nutrient-management zones—to safeguard this critical coastal groundwater resource